TATA KELOLA ADAPTIF WILAYAH PESISIR: META TEORI ANALISIS - Lesmana Rian Andhika (Balitbangda Provinsi Lampung, 2021)
Adaptive governance involves and directs performance towards achieving results in an increasingly competitive environment. Coastal zones and natural resources are important to be managed, offering opportunities and challenges to enhance sustainable economic, socio-cultural development. The purpose of this study is to explore various cases related to the management of coastal areas. Specifically, to adaptive governance that has developed as an analytical approach to understanding natural resource that takes its foundation from social and ecological system dependence. Meta Theory is used to provide arguments for the dimensions of adaptive governance. Several cases were chosen deliberately to strengthen the research argumentation. Thus, the use of adaptive governance in coastal zone provides opportunities for community to manage various coastal area issues. Therefore, this study provides information that the trend to increase community involvement is greater. Adaptive governance of coastal zone provides new economic growth for local communities. Local wisdom plays an important role in bringing the stability of moderation brought about in adaptive governance itself.